Vaso-occlusive crises in patients with sickle cell disease: Parents' perspectives and association with disease outcomes - Mohammed Zolaly, ABP; Ghaidaa Al-Mohammadi, MBBS; Ghadi Al-Saadi, MBBS; Danya Qasim, MBBS (Journal of Taibah University Medical Sciences, 2019)
الملخص: أهداف البحث: لقد تم تسجيل ارتفاع في نسبة انتشار الإصابة بمرض الخلايا المنجلية في المملكة العربية السعودية. ويعتبر أكثر المضاعفات شيوعا لدى الأطفال الذين يعانين من مرض الخلايا المنجلية هو الآلام الناجمة عن أزمات انسداد الأوعية الدموية، التي تحدث عندما تتجمع خلايا الدم الحمراء المصابة وتسبب احتشاءات في الاوعية الدموية الصغيرة. تهدف هذه الدراسة إلى تقييم مستوى الوعي حول أزمة انسداد الأوعية الدموية بين آباء مرضى الأنيميا المنجلية في منطقة المدينة المنورة وتأثير ذلك على أعراض المرض. طرق البحث: دراسة مقطعية، أجريت باستخدام استبانة منظمة ومحققة. شملت العينة ١٢٣ مشاركا، من آباء أطفال مصابين بالأنيميا المنجلية تتراوح أعمارهم بين ٢ إلى ١٨ عاما يعيشون في منطقة المدينة المنورة. النتائج: متوسط درجة المعرفة الكلية كان ٣٠ ±٤. حيث يتمتع غالبية الآباء (٧٤٪) بمستوى جيد من المعرفة. كان هناك ارتباط كبير بين مجموع نقاط المعرفة ونتائج المرض خلال العام الماضي للدراسة كما أظهر التحليل الإحصائي نتائج غير معتبرة بعد ربط المعرفة الكلية بتعليم الأب والأم وكذلك دخل الأسرة. يعتقد أولياء الأمور أن أفضل طريقة لزيادة الوعي بأزمة انسداد الأوعية الدموية هي اجتماعات التثقيف الصحي المباشرة بنسبة ٦٠.٩٧٪، بينما يعتقد ٣٠.٨٩٪ أن المعلومات المكتوبة أفضل، ويعتقد ٢١.١٣٪ أن الإنترنت سيكون خيارا جيدا لزيادة الوعي. الاستنتاجات: أظهرت الدراسة وجود وعي جيد عند آباء مرضى الانيميا المنجلية عن أزمات انسداد الأوعية الدموية. ولقد أثرت معرفة الآباء بطبيعة المرض على نتائج أزمة انسداد الأوعية الدموية في أطفالهم بشكل إيجابي. Abstract: Objectives: KSA has been reported to have a high prevalence of sickle cell disease (SCD). The most common complication of SCD in children is pain due to vaso-occlusion crises (VOCs) that ensue when sickle-shaped red blood cells are entrapped in small vessels, leading to infarcts. This study aimed to determine the level of awareness about VOCs among parents of patients with SCD and its correlation with the disease outcomes. Methods: A cross-sectional study was conducted including 123 parents of children with SCD, aged 2–18 years old. All recruited participants were residents of Almadinah Almunawwarah. A structured and validated questionnaire was used for data collection. Results: The mean total knowledge score was 30 ± 4. The majority of parents (74%) had a good level of knowledge about SCD. There was a significant association between the total knowledge score and the outcome of VOCs during the year prior (p < 0.05). There was no association between the total knowledge score and the parents' education and family income. Regarding methods of increasing awareness of VOCs, 60.97% of parents thought that the best method was by direct meetings about health education, while 30.89% preferred to have written information about the disease. Only 21.13% argued that the internet was a better choice for raising awareness. Conclusion: In this study, the parents of SCD patients had a good level of knowledge about VOCs. There was a significant association between the parents' awareness of VOCs and a better disease outcome in their children, as they had fewer attacks and hospital admissions. الكلمات المفتاحية: أزمة انسداد الأوعية الدموية, فقر الدم المنجلي, الاحتشاء, معرفة الوالدين, الأطفال, Keywords: Children, Infarction, Parents' awareness, Sickle cell disease, Vaso-occlusive crisis